ANALISIS PENGARUH TEKNOLOGI KECERDASAN BUATAN TERHADAP PENYEBARAN BERITA HOAX DI MEDIA SOSIAL - Renaldi, Alfin; Imayan, Rifki; Muda, Mas; Razzaq, Abdur (Pusat Penelitian dan Pengabdian (P3M) STKIP Majenang, 2025)
In this article, a comprehensive review of literature from 25 sources spanning the years 2020–2025 is used to study the impact of artificial intelligence (AI) technology on the spread of fake news on social media. AI algorithms on platforms like Facebook and Twitter prioritize emotional content, causing fake news to spread 6 times faster than real news, according to qualitative content analysis. Automated chatbots were responsible for 40% of hoax comments in the 2016 US and 2024 Indonesian election disinformation campaigns, while AI-based deepfake technology produced manipulative videos that convinced 78% of users. 61% of viral hoax trends on Twitter originated from AI bots with a Botometer score of over 0.7. If used as a